Design, docking, synthesis and anticancer activity of some novel 2-(4-methylbenzenesulphonamido)pentanedioic acid amide derivatives - Satyajit Dutta; Deepak Kumar; Anand Kumar Mishra; Supratim Ray; K. Nagarajan (Bangladesh Pharmacological Society, 2014)
In the present work few novel 2-(4-methylbenzenesulphonamido)pentanedioic acid amide derivatives and the basic compound 2-(4-methylphenylsulfon-amido)pentanedioic acid have been designed, synthesized, characterized and screened for their possible antineoplastic activity both in vitro and in vivo. The modified drugs were docked against the protein histone deacetylase the energy value obtained was o-iodoanilide (-10.370504) and m-iodoanilide (-10.218276) of the titled compound. The in vitro activity was performed against five human cell lines like human breast cancer (MCF-7), leukemia (K-562), ova-rian cancer (OVACAR-3), human colon adenocarcinoma (HT-29) and Human kidney carcinoma (A-498). The in vivo activity was performed in female Swiss albino mice against Ehrlich Ascites Carcinoma (EAC). Among the synthesized compounds, o-iodoanilide, m-iodoanilide and p-iodoanilide derivatives of 2-(4-methyl benzene sulphonyl)-pentanedioic acid amides showed encouraging activity in both the in vitro and in vivo compared to other compounds.